2014
DOI: 10.2319/062714-463.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic assessment of lower third molar eruption in different anteroposterior skeletal patterns and age-related groups

Abstract: Objective: To analyze radiographic predictors for lower third molar eruption among subjects with different anteroposterior skeletal relations and of different age groups. Materials and Methods: In total, 300 lower third molars were recorded on diagnostic digital orthopantomograms (DPTs) and lateral cephalograms (LCs). The radiographs were grouped according to sagittal intermaxillary angle (ANB), subject age, and level of lower third molar eruption. The DPT was used to analyze retromolar space, mesiodistal crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
14
1
1
Order By: Relevance
“…6,24 Other associated Class II skeletal characteristics are an acute gonial angle and a narrow mandible. 6 Likewise, it is expected that the space-to-width ratio in Class III patients will attain the values needed for eruption of the lower M3, thus acting as a protective factor against impaction, 9 even though this was not confirmed by our results. This disagreement may be attributed to how we evaluated the sagittal relationship, in which we observed the dental relationship, versus how other studies evaluate dental and skeletal relationships.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…6,24 Other associated Class II skeletal characteristics are an acute gonial angle and a narrow mandible. 6 Likewise, it is expected that the space-to-width ratio in Class III patients will attain the values needed for eruption of the lower M3, thus acting as a protective factor against impaction, 9 even though this was not confirmed by our results. This disagreement may be attributed to how we evaluated the sagittal relationship, in which we observed the dental relationship, versus how other studies evaluate dental and skeletal relationships.…”
Section: Discussioncontrasting
confidence: 52%
“…These include amount of pretreatment crowding, 30 pattern of mandibular and condylar growth, available retromolar space and residual mandibular growth in Class III patients. 9 The clinical implications of our findings might guide clinical actions and improve the understanding M3 impaction behavior. In sum, mesioangulation of M3 and a pronounced overbite before orthodontic treatment are predictive dental and occlusal characteristics of future disturbances regarding M3 eruption, and indicate orthodontic treatment with premolar extraction in borderline cases.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, orthodontic anchoring screw has been generalized, and absolute anchorage can be achieved without active patient cooperation [6]. In a prior study, skeletal Class II patients showed a higher percentage of the impaction rate of third molars (62.3%) than did skeletal Class III patients (31.7%) [7]. They are mainly extracted because of incomplete eruption.…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies have reported third molar as one of the most commonly impacted tooth accounting for 98% of tooth impactions. 3,4 Mandibular third molar has more tendency for impaction as compared to maxilla. 5 It was noted that 3 to 4 years of ageis the time when crypt formation ofthird molar begins, while calcification starts at the age of 7 to 10 years.…”
Section: Introductionmentioning
confidence: 99%